An Exploration of Indonesian EFL Learners' Speaking Anxiety - Yuli Meliyani; Dhafid Wahyu Utomo; Masrupi Masrupi (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2022)
This research reports the factors that trigger Foreign Language Speaking Anxiety as perceived by Indonesian EFL learners. The qualitative method was employed in this research. The participants of this research were the 33 Indonesian EFL learners from the class X IPS 3 of SMAN 1 Pandeglang, year academic 2019-2020. The initial process of collecting the data was by spreading a questionnaire known as Foreign Language Anxiety Scale (FLCAS) developed by Horwitz et al. (1986). Then it was followed by an in-depth interview for the ten students with high anxiety levels based on their FLCAS Score. The data was then analysed through three steps developed by Miles and Huberman (1994). The triangulation technique was used to strengthen this research's credibility. This research found that the factors that could trigger students' anxiety are divided into two. The first is teacher-related factors such as assertive teaching and the teacher's calling method. The second is student-related factors such as their negative view of English, being mocked by friends, fear of making mistakes, self-confidence, and inadequate support to practice English speaking. To reduce anxiety, students need to be exposed to the target language as often as possible and get used to it to improve their confidence in speaking English. In addition, the teacher should always be able to find a way to make an entertaining and less tense classroom environment.